-4(a+3)-7=

Simple and best practice solution for -4(a+3)-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(a+3)-7= equation:


Simplifying
-4(a + 3) + -7 = 0

Reorder the terms:
-4(3 + a) + -7 = 0
(3 * -4 + a * -4) + -7 = 0
(-12 + -4a) + -7 = 0

Reorder the terms:
-12 + -7 + -4a = 0

Combine like terms: -12 + -7 = -19
-19 + -4a = 0

Solving
-19 + -4a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + -4a = 0 + 19

Combine like terms: -19 + 19 = 0
0 + -4a = 0 + 19
-4a = 0 + 19

Combine like terms: 0 + 19 = 19
-4a = 19

Divide each side by '-4'.
a = -4.75

Simplifying
a = -4.75

See similar equations:

| 114=-2x-8+5x | | 0=5-5y+7x | | 14x^2-46x+12=0 | | 4n+1=4n+1 | | 4x+6-7x+9=18 | | 6-(2n+3)-4n=6 | | 2x=5x-30 | | 12z-1=z^2+35 | | (x-9)+(.5x)=180 | | -3=3w-(4w+6) | | y^2+12y+20= | | 6=2(x+8)-5y | | 7x-8y=16 | | m^2+13m+40=0 | | 4x+5=11-3x | | -10x+3=5x-2 | | 3x-22= | | 2x-22= | | 3x-34= | | 3x^2-6x+2k=0 | | 3x=(x+1)(x+2)+8 | | 4(6+2x)=0 | | x+15=2(x-10) | | x+15=2(x-15) | | 8w-11=-8w | | 3x=11+1 | | -7x-10=-3x-14 | | 2x+2y=22 | | 8w+40=0 | | 3x+1y=20 | | 11.6b+2=3.8b+38.66 | | 11.4x+3=5.7x+28.08 |

Equations solver categories